1046 Anterior Lumbar Interbody Fusion Approaches: A Systematic Review. (12th October 2021) - Feeley, A; Feeley, I; Clesham, K; Butler, J
Abstract: Aim: Anterior lumbar interbody fusion (ALIF) is a well-established alternative to posterior-based interbody fusion techniques, with approach variations, such as retroperitoneal; transperitoneal; open; and laparoscopic well described. Variable rates of complications for each approach have been enumerated in the literature. We aim to elucidate the comparative rates of complications across approach type. Method: A systematic review of the search databases Pubmed; google scholar; and OVID Medline was made in November 2020 to identify studies related to complications associated with anterior lumbar interbody fusion. PRISMA guidelines were utilised for this review. Studies eligible for inclusion were agreed by two independent reviewers. Meta-analysis was used to compare intra- and postoperative complications with ALIF for each approach. Results: 4575 studies were identified, with 5728 patients across 31 studies included for review following application of inclusion and exclusion criteria. Meta-analysis demonstrated the transperitoneal approach resulted in higher rates of Retrograde Ejaculation (RE) (p < 0.001; CI = 0.05-0.21) and overall rates of complications (p = 0.05; CI = 0.00-0.23). Rates of RE were higher at the L5/S1 intervertebral level. Rates of vessel injury were not significantly higher in either approach method (p = 0.89; CI=-0.04-0.07). Laparoscopic approaches resulted in shorter inpatient stays (p = 0.01). Conclusions: Despite the transperitoneal approach being comparatively underpowered, its use appears to result in a significantly higher rate of intra- and postoperative complications, although confounders including use of BMP and spinal level should be considered. Laparoscopic approaches resulted in shorter hospital stays, however its steep learning curve and longer operative time have deterred surgeons from its widespread adaptation.